PENGEMBANGAN PROTOTYPE PENGONTROLAN LAMPU VIA ANDROID SEBAGAI MEDIA PEMBELAJARAN DI SMK DWIWARNA MEDAN - Sirait, Wanjul Fransisco; Amin, Muhammad (Universitas Negeri Medan, 2023)
Abstract This research aims to develop learning media using light control prototypes in microcontroller and microprocessor engineering subjects at Dwiwarna Vocational School, Medan. The research method used is the research and development method with the ADDIE development research model. The stages in development are 1) Analysis Stage, 2) Design, 3) Development or Production, 4) Implementation or Delivery, 5) Evaluations. Data collection for validation of learning materials and media uses a Likert scale. The results of this development research are a light control prototype along with a job sheet. This prototype-based learning media has gone through the validation test stage with an average achievement percentage of 85% according to material experts and 88.12% according to media experts. From the research results, it can be concluded that the learning media using the lamp control prototype meets the quality requirements and is suitable for use as a media to support learning activities for microprocessor and microcontroller programming. Key Words: Learning Media, Light Control Prototype AbstrakPenelitian ini bertujuan untuk mengembangnkan media pembelajaran menggunakan Prototype pengontrolan lampu pada mata pelajaran teknik mikrokontroller dan mikroprosesor di SMK Dwiwarna Medan Metode penelitian yang digunakan adalah metode penelitian dan pengembangan (research and development ) dengan model penelitian pengembangan ADDIE. Tahapan dalam pengembangannya yaitu 1) Tahap Analysis, 2) Design, 3) Development or Production, 4) Implementation or Delivery, 5) Evaluations. Pengambilan data validasi materi dan media pembelajaran menggunakan skala likert. Hasil dari penelitian pengembangan ini berupa Prototype pengontrolan lampu berserta Jobsheet . media pembelajran berbasisi prototype ini telah melalui tahap uji validasi dengan rata – rata persentase capaian sebesar 85 % menurut ahli materi dan 88,12 % menurut ahli media. Dari hasil pnelitian dapat disimpulkan bahwa media pembelajaran menggunakan Prototype Pengontrolan lampu ini memenuhi syarat dengan kualitas Layak untuk digunakan sebagai media penunjang kegiatan pembelajaran pemograman mikroprosesor dan mikrokontrollerKata kunci : Media Pembelajaran, Light Control Prototype